Clonorchis sinensis extracellular vesicles associated with Csi-let-7a-5p activate pro-inflammatory macrophages to induce biliary injury. - Beibei Zhang; Xing Li; Qian-Yang Zhou; Chen Zhang; Zheng-Rui Bian; Xin-Xin Ren; Qian Yu; Hui Hua; Zhihua Jiang; Bo Zhang; Xiang-Yang Li; Mu-Xin Chen; et al. (PLoS Neglected Tropical Diseases)
During Clonorchis sinensis (C. sinensis) infection, pro-inflammatory macrophages (M1 macrophages) are highly activated, yet their role in the disease remains poorly understood. Previous studies have demonstrated that extracellular vesicles from C. sinensis (CsEVs) can activate these macrophages, and inhibiting a specific miRNA (Csi-let-7a-5p) in CsEVs (InCsEVs) can reduce this activation. In the present study, liver macrophages in mice were removed using clodronate liposomes (Clodlip). Subsequently, different types of bone marrow-derived macrophages (BMDMs) were adoptively transferred into the mice lacking liver macrophages: untreated (PBS-BMDM), treated with CsEVs (CsEVs-BMDM), treated with a control (ScrCsEVs-BMDM), or treated with InCsEVs (InCsEVs-BMDM). Biliary damages were then evaluated. The results indicated that the transferred macrophages successfully repopulated the mice. CsEVs-BMDM led to significant inflammation and bile duct damage, accompanied by higher levels of inflammatory cytokines (TNF-α and IL-1β). However, when macrophages were treated with InCsEVs, the damage and inflammation were alleviated, and the levels of TNF-α and IL-1β decreased. These findings suggest that pro-inflammatory macrophages activated by CsEVs, especially through Csi-let-7a-5p, play a crucial role in biliary damage during C. sinensis infection. Although other immune cells may also be involved, this study emphasizes the significance of pro-inflammatory macrophages in clonorchiasis.